Simulasi Pengendali Filter Aktif Sebagai Upaya Memperbaiki Kualitas Daya Listrik Di Laboratorium Teknik Listrik Politeknik Negeri Pontianak - Suharto, Irawan (ELKHA : Jurnal Teknik Elektro, 2013)
Abstract Non linier loads are widely used in Electrical Engineering Laboratories of State Polytechnic of Pontianak. The measurement using Power Quality meter produces the voltage harmonic level which meets the Standard of IEEE 519 - 1992, that is, less than 5 %. However, the current harmonic level measured are varies for each phase where the lowest harmonic level is 6.01% and the highest one is 59 %. These do not meet the harmonic standard of IEEE 519-1992. In order to solve the problem, it has been conducted a simulation using shunt active filter based on the theory proposed by Akagi. The result of simulation conducted to the loads shows a decrease of harmonic current level of 2.24% in phase R, 1.66% in the S phase and 1.91% in phase T. The current's THD occurred from the simulation results has met the standard of IEEE 519-1992. Keywords Non linier, Harmonic, active filter, THD